Respostas
respondido por:
0
2x² - 9x + 3x² - 17x - 7
2x² + 3x² - 9x - 17x -7
5x² - 26x - 7 = 0
a = 5 b = -26 c = -7
∆ = b² - 4.a.c
∆ = -26² - 4 * 5 * -7
∆ = 676 + 140
∆ = 816
x = (-b ± √∆) ÷ 2.a
x' = (26 + √816) ÷ 2.5
x' = (26 + 28,56) ÷ 10
x' = 54,56 ÷ 10
x' = 5,45
x" = (26 - √816) ÷ 2.a
x" = (26 - 28,56) ÷ 10
x" = -2,56 ÷ 10
x" = -0,25
Espero ter ajudado, estou a disposição no chat para dúvidas, bons estudos e boa sorte
2x² + 3x² - 9x - 17x -7
5x² - 26x - 7 = 0
a = 5 b = -26 c = -7
∆ = b² - 4.a.c
∆ = -26² - 4 * 5 * -7
∆ = 676 + 140
∆ = 816
x = (-b ± √∆) ÷ 2.a
x' = (26 + √816) ÷ 2.5
x' = (26 + 28,56) ÷ 10
x' = 54,56 ÷ 10
x' = 5,45
x" = (26 - √816) ÷ 2.a
x" = (26 - 28,56) ÷ 10
x" = -2,56 ÷ 10
x" = -0,25
Espero ter ajudado, estou a disposição no chat para dúvidas, bons estudos e boa sorte
Perguntas similares
6 anos atrás
6 anos atrás
8 anos atrás
9 anos atrás